Hematologies : The Political Life of Blood in India - Copeman, Jacob; Banerjee, Dwaipayan, 1983- (Book collections on Project MUSE., 2019)
"Hematologies examines how the giving and receiving of blood has shaped social and political life in north India in the twentieth and twenty-first centuries"--